2021
DOI: 10.46338/ijetae1221_17
|View full text |Cite
|
Sign up to set email alerts
|

The Influence between GIS Quality and user Satisfaction towards Individual Work Performance: A Proposed Conceptual Framework.

Abstract: Abstract— In this Industrial Revolution 4.0 (IR 4.0) era, information systems are widely used by organizations to understand and plan their operations efficiently. One of the trends used in organizations is the Geographical Information System (GIS). GIS is meant to be an element of location intelligence where it is viewed as a tool for organizations to visualize, understand, and analyze data. GIS benefits users in understanding data efficiently with minimal cost and improving work performance. However, based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…In the ISO/IEC 25030 standard, functional requirements define software quality requirements that determine how well software performs. So, the quality requirements indicate how much the software can provide and maintain the specified service [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ISO/IEC 25030 standard, functional requirements define software quality requirements that determine how well software performs. So, the quality requirements indicate how much the software can provide and maintain the specified service [6].…”
Section: Introductionmentioning
confidence: 99%
“…The minimum quality rating standard for web applications is 70 [6]. So, it can be concluded that the ITS Academic Information System has met the quality standards on the characteristics of Functional Suitability, Performance Efficiency, and Reliability.…”
mentioning
confidence: 96%